Determinant Factors of Tax Compliance Level of Boarding House Business Owners in Supporting Locally-Generated Revenue of Semarang - Pratiwi Princesswara; Deden Dinar Iskandar (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2019)
The research aims to examine the influencing factors of tax compliance of boarding house owner. This research uses one dependent variable which is Tax Compliance and seven independent variables which consist of income, environment, tax sanctions, tax services & appeals, tax awareness, perception on transparency of tax usage & allocation, and perception & accountability of efficiency of tax payment system. The primary data collected with questionnaire towards 82 respondents who’s elected by a random sampling. Data was analyzed with a multiple linear regression by SPSS version 22. The result showed that: (1) The variables of Income, tax services & appeals, perception on transparency of tax usage & allocation, and perception & accountability of efficiency of tax payment system are significantly influence the tax compliance of taxpayer in Semarang, (2) Variables of environment, Tax sanctions and Tax awareness are insignificantly influence the tax payment of taxpayer in Semarang. Semarang government is expected to be able to increase boarding house tax in order to increase its locally-generated revenue